2016
DOI: 10.2147/ndt.s97249
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of postoperative delirium in elderly patients undergoing transurethral resection of prostate: a prospective cohort study

Abstract: AimThe aim of the present study was to investigate the occurrence of postoperative delirium (POD) in elderly patients undergoing transurethral resection of prostate (TURP) and to identify those factors associated with delirium.MethodsFrom July 2010 to February 2015, 358 patients, aged ≥65 years and undergoing TURP were prospectively enrolled. Personal, medical and cognitive data, laboratory assessments, pain intensity, preoperative medications, and details of hemodynamic control were collected as predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 22 publications
1
71
1
1
Order By: Relevance
“…Tai et al . and Xue et al . reported that the incidences of postoperative delirium associated with TURP were 21.2% and 7.8%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Tai et al . and Xue et al . reported that the incidences of postoperative delirium associated with TURP were 21.2% and 7.8%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The other potential explanation is differences in the definition of delirium among studies. In other studies, delirium was assessed using the Confusion Assessment Method or Diagnostic and Statistical Manual of Mental Disorders‐IV . We used the ICDSC, which can be easily employed by a clinician or a nurse to screen all patients even when communication is compromised .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations